2021
DOI: 10.1186/s13063-021-05247-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acupotomy in knee osteoarthritis patients: study protocol for a randomized controlled trial

Abstract: Background Symptomatic knee osteoarthritis (KOA) is common in China. Pharmacological therapy is not the first recommendation because of its safety issues. Nonpharmacological therapy, such as lifestyle adjustments, weight loss, muscle strengthening, and aerobic exercise programs, is strongly recommended for KOA. However, these approaches may fail due to poor patient compliance. There is a lack of high-quality randomized controlled trials of acupotomy, an effective treatment for KOA. This study w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In the sensitivity analyses of the included studies, we excluded two studies with greater heterogeneity (27,29), which involved using bladed needles and needle knives with a loosening effect. Needle knives and bladed needles originated from the ancient "nine-needle" therapy, which differs from the round needle with a pointed tip of traditional acupuncture, with a thicker diameter and a flattened and bladed tip, except for the effect of regulating qi and blood of the traditional acupuncture, which can peel off and loosen the adhesion, contracture of the tendons, and relieve the nerve and blood vessel from the pressing stimulation (38)(39)(40)(41). The study revealed that the needle knife with loosening effect and blade needle have a better effect on improving the functional status of patients' waist; however, we included fewer studies with smaller sample sizes, and the research data to argue the possibility of the cause of this heterogeneity are insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…In the sensitivity analyses of the included studies, we excluded two studies with greater heterogeneity (27,29), which involved using bladed needles and needle knives with a loosening effect. Needle knives and bladed needles originated from the ancient "nine-needle" therapy, which differs from the round needle with a pointed tip of traditional acupuncture, with a thicker diameter and a flattened and bladed tip, except for the effect of regulating qi and blood of the traditional acupuncture, which can peel off and loosen the adhesion, contracture of the tendons, and relieve the nerve and blood vessel from the pressing stimulation (38)(39)(40)(41). The study revealed that the needle knife with loosening effect and blade needle have a better effect on improving the functional status of patients' waist; however, we included fewer studies with smaller sample sizes, and the research data to argue the possibility of the cause of this heterogeneity are insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…KOA is a prevalent ailment that canlead to substantial debilitation, yet the underlying etiology of KOA remains enigmatic. Research has revealed that the degeneration of articular cartilage and alterations in synovial composition are pivotal pathological changes associated with this condition (19). Clinical guidelines offer divergent recommendations (10)(11)(12) encompassing both pharmacological and nonpharmacological interventions to address the symptoms of KOA.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidences proved that acupotomy therapy was an effective treatment for KOA [ 14 – 16 ]. For example, Wang et al (2019) reported that the application of acupotomy clearly alleviated the symptoms of KOA in rabbits by changing the arrangement of fibrous tissue [ 8 ].…”
Section: Discussionmentioning
confidence: 99%